RESEARCH OF MATHEMATICAL MODEL FOR OPERATIONS TO DETERMINE RISKS FOR PROTECTIONS OF CRITICAL INFRASTRUCTURE - Pashov, Lyubomir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
This work is a research of the mathematical model for operations to determine the risk to critical infrastructure protection. We introduce the concept of determined uncontrollable factors, providing an opportunity to differentiate some variables, which cannot be influenced by the operating party in any way. The random factors are considered known for their distribution function. Particular attention is paid to the mathematical models which are classified as dynamic or static, depending on their specific characteristic.